Mitochondria: Endosymbiont bacteria DNA sequence as a target against cancer. Issue 12 (4th October 2021) - Nagase, Hiroki; Watanabe, Takayoshi; Koshikawa, Nobuko; Yamamoto, Seigi; Takenaga, Keizo; Lin, Jason
Abstract: As the energy factory for the cell, the mitochondrion, through its role of adenosine triphosphate production by oxidative phosphorylation, can be regarded as the guardian of well regulated cellular metabolism; the integrity of mitochondrial functions, however, is particularly vulnerable in cancer due to the lack of superstructures such as histone and lamina folds to protect the mitochondrial genome from unintended exposure, which consequently elevates risks of mutation. In cancer, mechanisms responsible for enforcing quality control surveillance for identifying and eliminating defective mitochondria are often poorly regulated, and certain uneliminated mitochondrial DNA (mtDNA) mutations and polymorphisms can be advantageous for the proliferation, progression, and metastasis of tumor cells. Such pathogenic mtDNA aberrations are likely to increase and occasionally be homoplasmic in cancer cells and, intriguingly, in normal cells in the proximity of tumor microenvironments as well. Distinct characteristics of these abnormalities in mtDNA may provide a new path for cancer therapy. Here we discuss a promising novel therapeutic strategy, using the sequence‐specific properties of pyrrole‐imidazole polyamide‐triphenylphosphonium conjugates, against cancer for clearing abnormal mtDNA by reactivating mitochondrial quality control surveillance. Abstract : Therapy based on PIP‐TPP's ability for mtDNA homing takes on a promising improved specificity for cancer and tumor microenvironment cells within whole tumor masses, especially for advanced cancers with homoplasmic mutations as well as other mitochondrial and aging diseases in the form of treatment and preventative care.